Developing a Digital Islamic Education Model: Integrating Artificial Intelligence, Islamic Pedagogy, and Digital Learning Ecosystems - Rahmat Zubandi Thahir; Hasan Baharun (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study investigates the integration of Artificial Intelligence (AI) and the subsequent transformation of the digital learning ecosystem within Islamic Education (PAI) at SMA 01 Tiris. Operating within a qualitative intrinsic case study design, this research explores how modern educational technologies can be adopted without reducing the foundational spiritual and affective dimensions of traditional Islamic pedagogy. Data were comprehensively gathered using method triangulation—comprising semi-structured in-depth interviews with key institutional stakeholders, participant observations of digital classroom dynamics, and documentary analysis of digital curricula and artifacts. The collected data were analyzed interactively using the Miles, Huberman, and Saldaña framework, while scientific trustworthiness was secured via source triangulation, technical triangulation, and member checking. The empirical findings reveal that the mechanism of AI integration does not lead to institutional secularization; instead, it establishes a framework of